IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NO. 8 TAHUN 2012 TENTANG RETRIBUSI IZIN GANGGUAN ( STUDI KASUS SPBU) - Antoni Tamba; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru city is one of the cities in Indonesia are experiencing a rapid increase in business development and investment in Indonesia. Disturbance Permit be one important factor in obtaining legality of local authorities towards the establishment of a business. Appropriation nuisance permit (HO) aims to protect the public interest and to maintain order and as a form of government oversight and pengedalian in certain locations which may cause hazards losses and disruption. Establishment of a gas station in the city of Pekanbaru often cause problems with the surrounding community. On the other hand there are many gas station stations that have not paid levies nuisance permit (HO). Integrated Service Agency and Investment (BPTPM) Pekanbaru City as an institution designated by the city of Pekanbaru who has authority in the permitting process and the levy charged for this permit in accordance with Regulation City of Pekanbaru No. 8 in 2012 regarding Disturbance Permit.Based on these findings, this study aims to determine the extent of implementation and the factors that affect the implementation of Pekanbaru City Regional Regulation No. 8 in 2012. This study uses the theory of implementation by Van Meter and Van Horn who has six variables, standards and objectives, resources, characteristics of the implementing agencies, communication between organizations, socio-economic conditions and political and disposition. The method used in this research is qualitative research. With the technique performed is purposive sampling to key informants. In this study, the informant is BPTPM, Disperindag Pekanbaru and related institutions. In gathering the data used qualitative approach with the method of observation and interviews, after the data is collected then analyzed by descriptive.Based on the research that has been carried out based on theoretical concepts, the implementation of Local Regulation No. 8 in 2012 Licenses Disorders at the Gas Stations, has been implemented by BPTPM. However, implementation of the regulations are not well realized. Weak sanctions make local regulation of fee collection process is not going well. The lack of resources in the form of personnel and technical team in the field also affects the implementation of the local regulation.Keywords: Implementation, Regulation, levies nuisance permit, gas stations